Online monitoring of coal particle size and flow distribution in coal-fired power plants: Dynamic effects of a varying mill classifier speed. (5th April 2016) - Blondeau, J.; Kock, R.; Mertens, J.; Eley, A.J.; Holub, L.
Highlights: The effect of a coal mill classifier speed was measured online in a 660 MWe plant. The coal particle fineness and the coal flow distribution were monitored. The amount of particles <75 µm varied between 66 and 74%. The maximum coal flow deviation was reduced from 14% to 9%. Abstract: The fineness of the coal powder and the uniformity of the coal flow sent to the burners are crucial parameters to achieve an effective combustion in coal-fired power plants. This study presents a methodology for the online monitoring of the (i) coal particle size distribution and (ii) coal flow distribution between burners at the outlet of a roller mill installed in 660 MWe coal-fired power plant. The effect of a varying centrifugal classifier speed on these two properties was investigated. To the best knowledge of the authors, it is the first time that such an effect is monitored online in a large scale utility boiler. For a classifier speed between 73 and 99 rpm, the mass fraction of particles smaller than 75 µm varied between 66 and 74%. The coal flow distribution between burners was strongly improved when the particle size was the smallest: the maximum deviation from the average flow rate was reduced from 14% at 73 rpm to 9% at 99 rpm.